Plant cholesterol biosynthetic pathway overlaps with phytosterol metabolism - Sonawane, P. D.; Pollier, J.; Panda, S.; Szymanski, J.; Massalha, H.; Yona, M.; Unger, T.; Malitsky, S.; Arendt, P.; Pauwels, L.; Almekias-Siegl, E.; Rogachev, I.; et al. (Nature Plants, 2017)
The amount of cholesterol made by many plants is not negligible. Whereas cholesterogenesis in animals was elucidated decades ago, the plant pathway has remained enigmatic. Among other roles, cholesterol is a key precursor for thousands of bioactive plant metabolites, including the well-known Solanum steroidal glycoalkaloids. Integrating tomato transcript and protein co-expression data revealed candidate genes putatively associated with cholesterol biosynthesis. A combination of functional assays including gene silencing, examination of recombinant enzyme activity and yeast mutant complementation suggests the cholesterol pathway comprises 12 enzymes acting in 10 steps. It appears that half of the cholesterogenesis-specific enzymes evolved through gene duplication and divergence from phytosterol biosynthetic enzymes, whereas others act reciprocally in both cholesterol and phytosterol metabolism. Our findings provide a unique example of nature's capacity to exploit existing protein folds and catalytic machineries from primary metabolism to assemble a new, multi-step metabolic pathway. Finally, the engineering of a 'high-cholesterol' model plant underscores the future value of our gene toolbox to produce high-value steroidal compounds via synthetic biology.